2020
DOI: 10.3389/fmolb.2020.576269
|View full text |Cite
|
Sign up to set email alerts
|

Pan-Cancer Analyses Reveal Prognostic Value of Osteomimicry Across 20 Solid Cancer Types

Abstract: Background: Osteomimicry of cancer cells had been widely reported in prostate cancer and breast cancer. However, the prognostic value of osteomimicry in various cancer types remained unclear. We hypothesized that osteomimicry would result in remodeling of the tumor microenvironment and was eligible to predict patient prognosis. Methods: A comprehensive transcriptomic analysis of the osteomimicry, which was characterized by mRNA expression of SPARC, SPP1, and BGLAP, across 20 solid tumors (7564 patients) using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…ATP7B is not only involved in tumour progression, but also in the development of platinum drug resistance (14)(15)(16). A previous study reported that BGLAP was associated with advanced breast cancer staging (17). P2RX4 belongs to the P2 purinergic receptor family, which is commonly upregulated in a variety of tumours and is associated with poor prognosis (18).…”
Section: Discussionmentioning
confidence: 99%
“…ATP7B is not only involved in tumour progression, but also in the development of platinum drug resistance (14)(15)(16). A previous study reported that BGLAP was associated with advanced breast cancer staging (17). P2RX4 belongs to the P2 purinergic receptor family, which is commonly upregulated in a variety of tumours and is associated with poor prognosis (18).…”
Section: Discussionmentioning
confidence: 99%
“…Currently, data regarding the value of SPARC expression as an outcome biomarker for the various molecular subtypes of breast cancer is limited and inconsistent [22,23,51,54]. While some studies have observed that high SPARC expression was associated with poor prognosis and worse EFS and OS in several histological types [19][20][21]50,55], other studies have shown an association between low levels of SPARC and worse survival [56,57]. In their recent meta-analysis considering SPARC expression and prognosis in breast cancer, Shi et al [57] showed that low SPARC expression correlated with worse overall and distant metastasis survival rates in grade 1/2 tumors, HER2-positive tumors, and luminal A subtype tumors.…”
Section: Discussionmentioning
confidence: 99%
“…This in turn promotes osteoclast-mediated bone resorption through the production of RANK-L, IL-2β, IL-6, IL-11 and tumor necrosis factor (TNF)-α, and supports evasion of an immune response [ 82 , 83 , 84 ] ( Figure 1 ). Besides breast cancer, osteomimicry has been observed across various bone metastatic cancers including prostate cancer and osteosarcoma [ 85 ].…”
Section: Mechanisms Of Metastasismentioning
confidence: 99%